2014
DOI: 10.1159/000365537
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Health-Related Quality of Life by Comprehensive Cancer Pain Therapy: A Pilot Study with Breast Cancer Outpatients under Palliative Chemotherapy

Abstract: Background: Cancer-related pain is highly prevalent among outpatients with metastatic breast cancer affecting their health-related quality of life (HRQoL). This study evaluates potential effects of comprehensive pharmacologic cancer pain therapy (CPT) on HRQoL. Patients and Methods: 52 outpatients with metastatic breast cancer undergoing palliative chemotherapy participated. 28 patients suffering from moderate to severe cancer pain were offered CPT. 13 patients participated (intervention group), and 15 decline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…4 Undertreatment of CP generates distress and impairs quality of life for patients. 5,6 Although evidence-based guidelines on therapeutic interventions exist, 7,8 data indicate that CP remains undertreated worldwide. 9,10 Inadequate assessment has been identified as a major contributor to undertreatment.…”
Section: Introductionmentioning
confidence: 99%
“…4 Undertreatment of CP generates distress and impairs quality of life for patients. 5,6 Although evidence-based guidelines on therapeutic interventions exist, 7,8 data indicate that CP remains undertreated worldwide. 9,10 Inadequate assessment has been identified as a major contributor to undertreatment.…”
Section: Introductionmentioning
confidence: 99%
“…These findings were confirmed by the results of Kroenke and Theobald [ 56 ]. Many studies also demonstrate that pain in breast cancer is associated with a lower HRQOL, especially in high levels of pain severity and pain interference, while good pain management led to an improved QOL [ 42 , 57 , 58 ]. Pain interference mostly affected normal work, walking ability, mood, sleep and general activity.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicates that fatigue, mucosal inflammation, proteinuria, hypertension, as well as gastrointestinal toxicity, occurred at a low frequency (32). Another previous study indicated that proteinuria, hypertriglyceridemia, diarrhea, and fatigue were the most common treatment-related TEAEs (33).…”
Section: Discussionmentioning
confidence: 99%